Teaching program based on the communicative approach to learning basic level of English as a foreign language in adult learners Chiclayo - 2016 - Usquiano Piscoya, María Magdalena (2017)
The research hereby aims to design a Teaching Program Model based on the Communicative Approach upon the Basic Level of English as a foreign language for adult learners focused on undergraduate educators of Cesar Vallejo University, at Chiclayo Campus, according to their learning preferences. In order to achieve this objective, a pretest has been settled to measure the knowledge level of the English language regarding the participants that constitute the sample and thence a questionnaire was adapted to gather their preferences on the learning strategies in relation to this language. The theoretical foundations addressed are the Communicative Approach, Constructivism, learning styles, andragogy, and the learning-teaching process on a teaching approach. An amount of 179 undergraduate educators constituted the population, and the sample, constituted of 100 educators, was selected through a simple random sampling method. Thereupon, the data analysis was executed and the discussion of the final research findings was done using Excel and the 19° version of the SPSS software. This information was processed taking into consideration the conclusions and the recommendations of this report. Subsequently, this research commenced to design the Teaching Program Model based on the Communicative Approach for the Basic Level of English as a foreign language for adult learners focused on undergraduate educators of Cesar Vallejo University, at Chiclayo Campus, according to their learning preferences. Such program was validated based on experts judgment, and it is presented through this report as an educational contribution and a departure point for future research.